Evaluation of Ecotourism Development Based on Community Based Tourism (CBT): A Study of the Nyarai Ecotourism Area, Padang Pariaman Regency - Alya Mahlil; Nora Eka Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to evaluate the development of ecotourism based on Community Based Tourism (CBT) at the Nyarai Ecotourism Area, managed under the coordination of the Tourism, Youth, and Sports Office of Padang Pariaman Regency, and to identify the internal and external constraints that hinder its development. The background of this study is rooted in the fact that although the Nyarai Ecotourism Area has received national and international recognition for its community-based conservation model, it still faces persistent problems in infrastructure, land status, fluctuating visitor numbers, and limited human resource capacity. This research employed a qualitative descriptive method with data collected through observation, in-depth interviews, and documentation involving informants from the Tourism Office, the village government, the Tourism Awareness Group (Pokdarwis), local business actors, and visitors, selected through purposive sampling. Data validity was examined using source triangulation, and data were analyzed through data reduction, data display, and conclusion drawing. The evaluation was carried out using William N. Dunn's six evaluation criteria (effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness), while the constraints were analyzed using Hansen and Mowen's constraint theory. The results show that the development of Nyarai Ecotourism has been effective, equitable, responsive, and appropriate in empowering the local community, but still faces structural challenges in efficiency and adequacy due to limited budget, facilities, and managerial capacity. The main internal constraints identified are human resources, facilities, and budget, particularly following the discontinuation of the Special Allocation Fund (DAK) since 2024, while the external constraints consist of protected forest status and complex inter-agency licensing regulations. This study recommends that the local government formulate a long-term development roadmap, diversify funding sources, and strengthen human resource capacity to ensure the sustainability of community-based ecotourism development.